Role of MRI in Evaluation of Spinal Trauma - Ameer Hassan Ubaid Hashem; Abdullah Ali Mahdi Mohammed; Hussain Muhammad Jasm; Basim Muhammad Khalif; Falah Ali Mohammed Dhahir (American Journal of Botany and Bioengineering, 2025)
Spinal trauma is a significant cause of morbidity and neurological disability, requiring accurate diagnosis for timely and effective treatment. Despite the availability of multiple imaging modalities, a gap remains in reliably detecting soft tissue and spinal cord injuries, particularly in the early stages. This study explores the diagnostic utility of Magnetic Resonance Imaging (MRI) in spinal trauma evaluation, emphasizing its advantages over radiography and computed tomography (CT). Through a comprehensive review of MRI techniques, sequences, and case studies, the research demonstrates MRI's superior contrast resolution in identifying disc herniation, ligamentous injury, spinal cord edema, and hemorrhage. Findings confirm that T1- and T2-weighted sequences are critical for evaluating neural and soft tissue integrity, significantly influencing surgical planning and prognosis. The results support MRI as the gold standard for spinal trauma imaging, advocating for its routine use in acute and chronic spinal injury management protocols.